Hyaluronate coating enhances the delivery and biocompatibility of gold nanoparticles. (15th April 2018) - Karakocak, Bedia Begum; Liang, Jue; Biswas, Pratim; Ravi, Nathan
Highlights: Gold nanoparticles (Au NPs) were coated with end-thiolated hyaluronic acid (HS-HA) to achieve an efficient homogeneous coating layer. Internalization of five different sizes of Au NPs (with and without HS-HA coating) was assessed. HA-specific CD44-rich cells (retinal epithelial and Chinese hamster ovary), as well as cells lacking CD44 receptors (NIH 3T3), were used. Confocal microscopy images showed that the 50- and 100-nm HS-HA-Au NPs were able to enter the cells; however, their nascent forms could not. HS-HA-Au NPs did not initiate apoptosis unlike uncoated Au NPs, and the amount of reactive oxygen species generation was significantly reduced. Abstract: For targeted delivery with nanoparticles (NPs) as drug carriers, it is imperative that the NPs are internalized into the targeted cell. Surface properties of NPs influence their interactions with cells. We examined the responses of retinal pigment epithelial cells, NIH 3T3 fibroblast cells, and Chinese hamster ovary cells to gold nanoparticles (Au NPs) in their nascent form as well as coated with end-thiolated hyaluronate (HS-HA). The grafting density of HS-HA on Au NPs was calculated based on total organic carbon measurements and thermal gravimetric analysis. We imaged the intracellular NPs by 3D confocal microscopy. We quantified viability and generation of reactive oxygen species (ROS) of the cells to Au NPs and monitored cell-surface attachment via electrical cell-substrate impedance sensing. The results confirmed that receptors on cell surfaces, for HA, are critical in internalizing HS-HA-Au NPs, and HA may mitigate ROS pathways known to lead to cell death. The 50- and 100-nm HS-HA-Au NPs were able to enter the cells; however, their nascent forms could not. This study shows that the delivery of larger Au NPs is enhanced with HS-HA coating and illustrates the potential of HA-coated NPs as a drug delivery agent for inflamed, proliferating, and cancer cells that express CD44 receptors.